Immunologic and Virologic Outcomes of Obese and Nonobese Incarcerated Adults on Antiretroviral Therapy for HIV Infection - Bunnell, Kristen L. (J Int Assoc Provid AIDS Care, 2018)
BACKGROUND: Obesity is common among patients with HIV. The objective of this study was to characterize response to antiretroviral therapy (ART) in a cohort of obese incarcerated adults compared to a nonobese cohort. METHODS: A retrospective matched cohort study was conducted in an HIV telemedicine clinic. Patients with body mass index (BMI) >30 kg/m(2) who received the same ART with >95% adherence for at least 6 months were matched to nonobese patients by age, gender, ART, CD4 count, and viral load at baseline. RESULTS: Twenty pairs were included, with an average BMI of 24 kg/m(2) in the nonobese cohort and 35 kg/m(2) in the obese cohort. No difference was observed in the proportion of patients who achieved virologic suppression or the change in CD4 count from baseline to 6 to 12 months. CONCLUSION: This study revealed no differences in immunologic recovery or virologic suppression between obese and nonobese patients in an adult correctional population.